Лигатуры для производства алюминиевых и магниевых сплавов - Напалков В. И. Виктор Иванович; Бондарев Б. И. Борис Иванович; Тарарышкин В. И. Виктор Иванович; Чухров М. В. Матвей Васильевич (Москва, Металлургия, 1983)
Авт. указаны на обороте тит. л.